Il cibo nella Divina Commedia - Serianni, Luca (Cuadernos de Filología Italiana, 2007)
In this essay a path is tracked through Dante’s masterpiece in search of allusions to food, in relation to the Medieval concept of gluttony and the punishment gluttons deserved in Hell and Purgatory. The terms hunger and food in the Divine Comedy are analysed with precise references to the expressions in the text; these words convey two different, opposite semantic values: one linked to the earthly world, which appears in the first two parts, and another figurative, expressing the thirst for an intellectual and moral knowledge, which is found in Paradise.